First Report of Cucurbita Blossom Blight and Fruit Rot Caused by Choanephora cucurbitarum in Mexico - Garcia-Estrada, Raymundo Saul (Plant disease, 2023)
In December 2022, blossom blight, abortion, and soft rot of fruits were observed on Cucurbita pepo L. var. Zucchini in Mexico under greenhouse conditions (temperatures of 10 to 32°C and relative humidity up to 90%). The disease incidence in about 50 plants analyzed was around 70% with a severity of nearly 90%. Mycelial growth on flower petals and fruit rot with brown sporangiophores was observed. Ten disinfested fruit tissues in 1% NaClO for 5 min and then rinsed twice in distilled water from the lesion edges were placed on potato dextrose agar culture medium (PDA) supplemented with acid lactic and then, the morphological characterization was carried out in V8 agar medium. After 48 h of growth at 27°C, the colonies were pale yellow with diffuse cottony mycelia that were non-septate and hyaline and produced both sporangiophores bearing sporangiola and sporangia. The sporangiola were brown, ranged from ellipsoid to ovoid, and had longitudinal striations that measured 22.7 to 40.5 (29.8) μm x 16.08 to 21.9 (14.5) μm long and wide, respectively (n=100). The sporangia were subglobose, had a diameter of 127.2 to 281.09 (201.7) μm (n=50), and contained ovoid sporangiospores that measured 26.5 to 63.1 (46.7) μm x 20.07 to 34.7 (26.3) μm long and wide, respectively (n=100) which had hyaline appendages at the ends. Based on these characteristics, the fungus was identified as Choanephora cucurbitarum (Ji-Hyun et al. 2016). For molecular identification, DNA fragments for the internal transcribed spacer (ITS) and the large subunit rRNA 28S (LSU) regions for two representative strains (CCCFMx01 and CCCFMx02) were amplified and sequenced with the primer pairs ITS1-ITS4 and NL1-LR3 (White et al. 1990; Vilgalys and Hester 1990). The ITS and LSU sequences were deposited in GenBank database (Accession numbers OQ269823-24 and OQ269827-28, respectively) for both strains. The Blast alignment showed from 99.84 to 100% identity with Choanephora cucurbitarum strains JPC1 (MH041502, MH041504), CCUB1293 (MN897836), PLR2 (OL790293), and CBS 178.76 (JN206235, MT523842). To confirm the specie identification, the evolutionary analyses were conducted from the concatenated sequences of the ITS and LSU of C. cucurbitarum and other mucoralean species with the Maximum Likelihood method and Tamura-Nei model included in the software MEGA11. The pathogenicity test was demonstrated using five surface-sterilized zucchini fruits inoculated with a sporangiospores suspension containing a concentration of 1 x 105 esp/mL on two sites per fruit (20 µL each) that previously were wounded with a sterile needle. For fruit control, 20 µL of sterile water was used. Three days after inoculation under humidity conditions at 27°C, white mycelia and sporangiola growth with a soaked lesion were observed. That fruit damage was not observed on the control fruits. C.cucurbitarum was reisolated from lesions on PDA and V8 medium which was confirmed by morphological characterization fulfilling Koch's postulates. Blossom blight, abortion, and soft rot of fruits caused by C. cucurbitarum were observed on Cucurbita pepo and C. moschata in Slovenia and Sri Lanka (Žerjav and Schroers 2019; Emmanuel et al. 2021). This pathogen has the capability to infect a wide variety of plants worldwide (Kumar et al. 2022; Ryu et al. 2022). There are no reports of C. cucurbitarum causing agricultural losses in Mexico, and this is the first report causing the disease symptoms in Cucurbita pepo in this country; however, this fungus was found in the soil of papaya-producing areas and it is considered an important plant pathogenic fungus. Therefore, strategies for their control are highly recommended to avoid spreading the disease (Cruz-Lachica et al. 2018)